Polyamorphism and Structural Transformation in Liquid B2O3 under Compression: Insight from Visualization of Molecular Dynamics Data - Lan, Mai Thi; Nhan, Nguyen Thu; Hong, Nguyen Van (VNU Journal of Science: Mathematics - Physics; Vol 30 No 1, 2014)
Abstract: The structural order, polyamorphism and structural change of liquid B 2 O 3 at 3000 K and in a 0-40 GPa pressure range are investigated by molecular dynamics simulation. Results show that the network structure of liquid B 2 O 3 is formed from BO x basic structural units (x=3, 4). At ambient pressure, most of basic structural units (coordination units) are BO 3 (over 99%). The BO 3 basic structural units are linked each to other via OB 2 linkages. At high pressure, the network structure of liquid B 2 O 3 comprises of both BO 3 and BO 4 units linked each to other via OB 2 or OB 3 linkages. The bond angle and bond length distribution in BO x units is not dependent of pressure. In other word, the topology structure of BO x units in different models is identical. The bond angle distribution in OB 2 linkages depends strongly on pressure meanwhile the bond angle distribution in OB 3 linkages does not depend on pressure. With increasing pressure, liquid B 2 O 3 transforms gradually from a BO 3 - network structure (at low pressure) to BO 4 - network structure (at high pressure). The distribution of BO x in model is not uniform but tends to form the clusters of BO x units. The clusters of BO 3 the form low density regions, conversely the clusters of BO 4 form the high density regions. The size of low and high density regions is strongly dependent of pressure. Keywords: Polyamorphism , molecular dynamics simulation , B 2 O 3 , structure.